2003
DOI: 10.1034/j.1600-0412.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms after anal sphincter rupture: a retrospective study

Abstract: Anal sphincter rupture is strongly associated with anal incontinence and dyspareunia several years postpartum. The complaints affect the daily lives of these women to a great extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 24 publications
4
13
1
1
Order By: Relevance
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductioncontrasting
confidence: 46%
“…To estimate a sample size, we used five studies that evaluated fecal incontinence after an anal sphincter tear [5,6,9,13,14]. Based on these studies, the overall fecal incontinence rate was 40% (21-57%) and 20% (7-32%) for women with and without an anal sphincter tear, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…35,36 We believe that our comparatively low incidence of postpartum faecal incontinence may have several explanations: Vigilance in detecting anal sphincter injuries may be comparatively high at our institution and it is departmental policy that all primary repairs are performed under regional anaesthesia in the operating theatre. Other reports may include patients whose repair was conducted under less optimal conditions, which may affect the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Studies show that OASR might have severe physical and physiological effects on women. [13][14][15][16] They reported feeling upset, tired, angry, resigned, frustrated and a sense of loss. They felt abandoned and vulnerable during labor and birth, suturing and the postpartum period as a result of the actions of their health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Despite the negative effects of OASR on women's daily lives few seek medical assistance. [15] Aim of the study The aim of this study was to describe women's experiences of living with ongoing severe difficulties of an OASR ≥ 8 weeks after delivery.…”
Section: Introductionmentioning
confidence: 99%